A TRAPEZIFOLIXANTHONE FROM STEM BARK OF Calophyllum soulattri COLLECTED FROM CENTRAL JAVA - Achadiyah, Tri Bintari; Handayani, Nestri; Wartono, M. Widyo (Alchemy Jurnal Penelitian Kimia, 2013)
A xanthone derivative namely trapezifolixanthone has been isolated and identified from EtOAc extract of stem bark ofCalophyllum soulattri. The maceration method was used to isolates the trapezifolixanthone then followed by fractionation method using vacuum liquid chromatography and purification process by flash chromatography. A 14 mg of yellowish oily solid was extracted. The compound was elucidated by 1H NMR, 13C NMR, and 2D NMR (HSQC, HMBC, COSY) supported by UV and IR spectroscopy. Base on spectral data and comparison with some references, it is known that the compound is trapezifolixanthone.